2012
DOI: 10.1530/erc-11-0351
|View full text |Cite
|
Sign up to set email alerts
|

Sorafenib in metastatic thyroid cancer

Abstract: Although thyroid cancer usually has an excellent prognosis, few therapeutic options are available in the refractory setting. Based on the recent results of phase II studies with tyrosine kinase inhibitors, we designed a retrospective analysis of patients with metastatic thyroid cancer treated with sorafenib in seven Spanish referral centers. Consecutive patients with progressive metastatic thyroid cancer (papillary, follicular, medullary, and anaplastic) not suitable for curative surgery, radioactive-iodine th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
65
3
5

Year Published

2013
2013
2023
2023

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 96 publications
(75 citation statements)
references
References 22 publications
2
65
3
5
Order By: Relevance
“…Grade 4: myocardial infarction and small-cell lung cancer Capdevila et al (2012) Grade 3: HFS (20) been studied as well, mainly comprising rosiglitazone, vorinostat, thalidomide, celecoxib, and selumetinib (Mrozek et al 2006, Ain et al 2007, Kebebew et al 2009, Woyach et al 2009, Ho et al 2013. Though most of them exhibited modest efficacy, selumetinib, a MAPK kinase (MEK) 1 and MEK 2 inhibitor, increased the uptake of iodine-124 in 12 of the 20 patients (60%).…”
Section: Discussionmentioning
confidence: 99%
“…Grade 4: myocardial infarction and small-cell lung cancer Capdevila et al (2012) Grade 3: HFS (20) been studied as well, mainly comprising rosiglitazone, vorinostat, thalidomide, celecoxib, and selumetinib (Mrozek et al 2006, Ain et al 2007, Kebebew et al 2009, Woyach et al 2009, Ho et al 2013. Though most of them exhibited modest efficacy, selumetinib, a MAPK kinase (MEK) 1 and MEK 2 inhibitor, increased the uptake of iodine-124 in 12 of the 20 patients (60%).…”
Section: Discussionmentioning
confidence: 99%
“…These findings have suggested that sorafenib may significantly improve outcomes in patients with DTC. Several Phase II trials have assessed the effects of sorafenib monotherapy in over 200 patients with thyroid cancer, most with DTC, with other patients having medullary and anaplastic carcinomas (14)(15)(16)(17)(18)(19)(20). The median progression-free survival (PFS) ranged from 14 to 24 months, with PR rates as high as 38%, and disease control rates (defined as SD plus PR) of 59%-100%.…”
Section: Adverse Eventsmentioning
confidence: 99%
“…Sorafenib in the form of oral tablets was permitted by the U.S. Food and Drug Administration (FDA) for use in the treatment of late-stage metastatic DTC in 2013. The effectiveness of sorafenib in DTC differs depending on the trial, and partial response (PR) rate ranges from 6% to 49% [62]. In a recent large trial progressive-free survival (PFS) reached 10.8% in I-131-resistant DTCs (compared to PFS 5.8% in a placebo group) [63].…”
Section: Szkolenie Podyplomowementioning
confidence: 99%